Formiranje Kosovelovega konstruktivizma - Vrečko, Janez (Primerjalna književnost, 2010)
This paper analyzes the dispute between Kosovel and Černigoj, which developed from the disagreement between Kandinsky and the constructivists at INHUK, which was then transferred to the dispute between Kandinsky and Moholy-Nagy at the Bauhaus school, and from here to Kosovel, following Černigoj's arrival in Ljubljana. The concepts of composition and construction are used to elucidate Černigoj's Ljubljana exhibit and the Trieste Constructivist Ambient, which Kosovel conceptually outlined in his poem "Kalejdoskop" (The Kaleidoscope) as early as 1924 and 1925 and formulated with the syntagm "metaphysical materialism". The dispute between suprematism and constructivism, which had already been resolved by Lissitzky, also experienced a resolution in Trieste in 1927 through Stepančič's mobiles and Malevich's White Square hung beneath the ceiling of the Ambient. This represented contact with the roots of constructivism, which Kosovel had achieved with his conses "x, y, z" and so on as early as 1924 and 1925. In this sense, the Trieste Constructivist Ambient also paid homage to Kosovel, a deceased poet and theoretician, because through his conses he achieved in literature what Černigoj could not in the fine arts.
Keywords: Kosovel, Srečko, 1904-1926; Trst; Černigoj, Avgust, 1898-1985; književnost; literature; likovna umetnost; visual arts; slovenska umetnost; slovenska poezija; literarna avantgarda; constructivism; konstruktivizem; likovne razstave